Industry-Institute Partnership-A Model - Mishrikoti, A. H.; Deshpande, P. P.; Telsang, M. T. (Journal of Engineering Education Transformations, 1997)
The need of industry and institute interaction is advocated at all levels. An attempt has been made In this paper to present a model for meaningful interaction. To cope with changing environment, Industry need to emphasise on manpower development through interaction with institutions.